Early results of cyanoacrylate adhesive ablation versus laser ablation for the treatment of great saphenous vein insufficiency in the Chinese mainland population. (April 2023) - Qi, Xiaotong; Zhang, Mingyi; Yu, Wu; Ran, Kun; Chen, Yikuan
Objective: In this study, we present our early outcomes of cyanoacrylate ablation (CA) versus endovenous laser ablation (EVLA) for the treatment of great saphenous vein (GSV) insufficiency in the Chinese mainland population. Methods: We retrospectively analyzed 108 patients (53 patients in the CA group and 55 patients in the EVLA group) with GSV insufficiency who were treated with CA and EVLA between May 2020 and May 2021. The Venous Clinical Severity Score and Aberdeen Varicose Vein Questionnaire were used to assess clinical symptoms and quality of life, respectively. Total closure rates and procedure-related adverse events were also recorded in both groups. Results: There was no significant difference between patients treated with CA or EVLA in terms of demographic and clinical characteristics. The average procedure time was 17 min in the CA group and 35 min in the EVLA group ( p < 0.001). The CA group had lower pain scores during the procedure and 3 days afterward than the EVLA group ( p < 0.001). At month 12, the CA group had a 90.4% closure rate, while the EVLA group had an 83.0% closure rate, with no significant difference between the two groups ( p > 0.05). There was no significant difference in the Venous Clinical Severity Score or Aberdeen Varicose Vein Questionnaire score between the groups ( p > 0.05). During follow-up, neither group experienced any significant adverse events, such as pulmonary embolism or deep venous thrombosis. The incidence of ecchymosis and paresthesia was significantly lower in the CA group than in the EVLA group ( p < 0.05). Conclusions: Cyanoacrylate ablation has a high feasibility profile and is an effective approach to accomplish complete GSV target vein closure at early follow-up in the Chinese patients. Compared to EVLA, the improvement in quality-of-life outcomes is also sustained and similar, with less pain and fewer complications due to the absence of tumescence anesthesia and postprocedural compression stockings.